أسباب ضعف الرواية عن الإمام أحمد كما يراها الخلال - الطريقي، عبدالرحمن بن علي بن سليمان (جامعة الملك سعود - كلية التربية, 2015)
يتناول هذا البحث جمع ما سطره أبو بكر، أحمد بن محمد الخلال (ت 311 ه)، حول تعقباته على رواة المسائل الفقهية عن الأمام أحمد فيما وجد من كتابه "الجامع الكبير"، ومن مدونات المذهب الحنبلي، فيما يخص تضعيفه لبعض الروايات المنقولة عن الأمام أحمد. وهذه التعقبات من الخلال تستدعي جمع متفرقها من تلك المصادر والمراجع، وإفرادها ببحث يجليها، ويقربها للباحثين . ورأيت أن أرد هذه التعقبات إلى ما يجمعها، فوجدتها ترجع إلى أسباب كثيرة، جرى إدراجها في سببين: الأول: أسباب تعود إلى الأمام أحمد، وهي : رجوع الأمام أحمد عن بعض الروايات، وهذا بحسب ما يقرره الخلال فقط، وورع الأمام أحمد فيما يختاره لنفسه و اسرته، ويفتي من سواهم بخلافه، وظهور قوة استدلال الأمام أحمد في رواية دون الأخرى، وإنكار الأمام أحمد ثبوت الدليل في بعض الروايات المنقولة عنه، ثم ينقل عنه ما يخالف إنكاره . الثاني : أسباب تعود إلى الراوي، وهي : تفرده بالرواية عن الأمام أحمد بما يخالف رواية الباقين، ومخالفة روايته لما يرويه الجماعة عن الأمام أحمد، وقدم سماع الراوي من الأمام أحمد، ووجود رواية متأخرة عنه، ونحو ذلك، وأخطاء بعض الرواة عن الأمام أحمد؛ كالغلط، والوهم، والسهو، وعدم الضبط، وعدم الفهم . فهذه الأسباب جعلها الخلال دليل ضعف الرواية التي اقترن بها سبب أو كثر من تلك الأسباب المذكورة، وقد دللت عليها بالأمثلة التي عثرت عليها.
This research is concerned with Abu-Bakr Al-Kallaal's views on what he considers weaknesses in conveying Imam Ahmad Ibn-Hanbal's jurisprudential works. It attempts to bring together those views for the benefit of researchers. It aims to gather the causes put forwanl by Al-Khallaal, explalliing the weaknesses in reporting hnam Ibn-Hanbal's jurisprudential views. It also aims to explain the terms used by Al-Khallaal in ranking some narratives on Ibn-Hanbal as dha'eef (weak). Thus, Al-Khallaal's great contribution to clarifying Ibn Hanbal's jurisprudential views can be acknowledged. The research starts with an inductive approach intracing the basic parts, then it moves on to a deductive approach to infer the causes of narrative weaknesses. Among the important findings of the research are the following: Al K.hallaal attributes weaknesses in reporting about Imam Ibn-Hanbal to Ibn-Hanbal himself and to narrators; on the imam's side are change of view, piety, varied strength of evidences and his rejection of evidence reliability; on the narrators' side are lone narrator, inconsistency with collective narratives, oldness of hearing narrative, and narrators' errors.
Keywords: الأحاديث النبوية -- رواية الحديث -- دراية الحديث